Peran Organisasi Gabungan Pemuda Pelajar Mahasiswa Barru (GAPPEMBAR) dalam Perpolitikan di Kabupaten Barru - Sulfiani, Sulfiani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to identify the role of the young student association of Barru toward political regional development. The observation uses descriptive qualitative approach and is conducted in Barru regency. Moreover, the purposive sampling method is applied to determine the informants participating in this study. Nine chosen informants that clearly understand the object analysis are interviewed for the data collection. Furthermore, the data analysis technique uses an interactive model consisting of data reduction, data presentation and data inference. The result shows that the role of the young student association of Barru into political are being unable to guard democracy as fairly as possible, they become critical and solutional partners for the government. They play an active role as polling station election organizer and election supervisors to ensure fraud will not occur. For those who have the political ability can develop themselves to strunggle in political parties to immediately hold the position of policy makers. Youth’s strategies to participate in the development involves forming cardres, working creatively, consistently and massively. Meanwhile, the obstacles encountered by gappembar in guarding process of democracy are as follows the poor relationship between young student association of Barru (GAPPEMBAR) organization committee and the alumni having a strategic position in the government sector. Moreover, government’s distrust toward GAPPEMBAR’s program causes them having limited access to take part in the preparation, execution, control and evaluation to political scene for development progress in Barru Regency.